Quantifying the Pain Experience in Hip and Knee Osteoarthritis. (2010) - Gandhi, Rajiv; Tsvetkov, Dmitry; Dhottar, Herman; Davey, J Roderick; Mahomed, Nizar N
Abstract : PURPOSE: The present study investigated whether the conceptualization of hip and knee osteoarthritis pain implicit in the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and Medical Outcomes Study Short-Form 36 (SF-36) scales is complete, or whether the addition of another scale, such as the Short-Form McGill Pain Questionnaire (MPQ-SF), provides a more complete characterization. Furthermore, the impact that mental health symptoms and catastrophizing had on these scales was investigated. METHODS: Before hip and knee arthroplasty, 200 patients completed surveys of demographic data, the WOMAC pain scale, the MPQ-SF, the SF-36 Bodily Pain scale, the Pain Catastrophizing Scale and the Hospital Anxiety and Depression Scale. Correlations between scales were calculated and linear regression modelling was used to determine the impact of mental health and catastrophizing on these three pain measures. RESULTS: A strong correlation between the WOMAC and SF-36 pain scales (r=−0.70) was found; however, both correlated only moderately with the MPQ-SF (r=0.36 and r=−0.36, respectively). Linear regression modelling showed that the Pain Catastrophizing Scale significantly predicted a greater score on all three pain scales (P<0.05). CONCLUSIONS: The addition of the MPQ-SF appears to add to a more complete quantification of the pain experience in hip and knee osteoarthritis.